Libriomancer - Hines, Jim C. (Hines, Jim C. Magic ex libris, 2012)
Gifted with the ability to draw objects out of books, Isacc Vainio, a Libriomancer, seeks assistance from a Harley-riding dryad after a number of vampire attacks are reported by other members of his secret, magic organization.